A DESCRIPTIVE STUDY ON INTERACTION IN SPEAKING CLASSROOM AT THE ELEVENTH YEAR OF SMK BINA PATRIA 1 SUKOHARJO IN 2008/2009 ACADEMIC YEAR - Kusumawati, Leny (2009)
This research paper is intended 1) to describe the teacher-students' interaction in English-speaking class at the eleventh year of SMK Bina Patria 1 Sukoharjo, especially class XI TP-3, and 2) to describe the problems faced by the teacher and student in their interaction. The researcher uses descriptive qualitative research. This study uses observation, interview, and document in collecting the data. The technique of analyzing the data is interactive-analysis model. The method of speaking classroom interaction is Flander's Interaction Analysis Categories (FIAC). The result of the study shows that teacher-student interaction in English-speaking class XI TP-3 of SMK Bina Patria 1 Sukoharjo is dominated by the teacher. There are some problems faced by the teacher, namely; the students do not want to take a risk, the students are less open-minded, the students do not have high motivation to learn, and limited instructional media. The problems faced by the students are students' limited vocabulary, students' grammar mastery.